Konflik Batin dalam Naskah Drama Rindu Ibu dan Nilai Pendidikan Karakter: Perspektif Carl Rogers - Jasmine Noer Aini; Wawan Hermawan2; Akhmad Fatoni (STIKes Ibnu Sina Ajibarang, 2025)
This study explores inner conflict in the drama script Rindu Ibu by Kukun Triyoga. It uses a descriptive qualitative approach with literary psychology methods. The analysis is based on Carl Rogers’ personality theory, focusing on organism, phenomenal field, and self. The findings show that characters experience psychological tension due to a mismatch between experience and self-concept. Mita faces the deepest conflict after being rejected by her biological mother. Character values such as honesty, courage, and empathy emerge in the emotional healing process.